Safety assessment of trees used as anchors in cable-supported tree harvesting based on experimental observations. (October 2019) - Marchi, Luca; Mologni, Omar; Trutalli, Davide; Scotta, Roberto; Cavalli, Raffaele; Montecchio, Lucio; Grigolato, Stefano
Abstract : In conventional cable-supported forest operations, trees and their stumps are normally employed as anchoring elements to withstand high lateral forces. These loads, even if applied near the stem base where cross-section is larger, are characterised by higher magnitude and dynamic amplification effects. Consequently, failures of anchors due to overturning or stem breakage are possible. To evaluate the load-carrying capacity of anchors processes similar to the techniques used for tree stability assessment were used for tree pulling tests, performed up to failure, on sound Norway spruce with medium-large diameter at breast height grown on mineral soil. To this aim, high-strength pulling equipment was designed and exploited to reproduce the loading conditions for trees used as anchors, while monitoring their movement using low-cost precision sensors. The obtained mechanical response of the tested trees was compared with the predictive statistical and analytical models available in the literature. The main results confirmed the difficulty of giving a direct, sufficiently accurate and non-site-specific prediction on their load carrying capacity. Therefore, a method of normalisation of some of the easily measurable parameters that can be obtained through a non-destructive pulling test was used. A procedure, aimed at providing a more accurate assessment of the stability of anchors to help to reduce the number of accidents in cable-supported harvesting operations, is proposed and discussed. Highlights: Development of a method to assess safety of trees as anchors in forest operations. Low-cost sensors are used to monitor root-plate rotation during tree pulling tests. Rotation at peak load appears to be less site-specific than peak resisting force. Normalization of moment vs. displacement curve is fundamental. The proposed method can be potentially applied in cable-supported forest operations.